Qur'anic Ecological Analysis of Wildlife and Biodiversity Protection - Rahmawati, Artifah Tomi; Nirwana, Andri; Nughroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The objective of this research is to examine the Qur’anic ecological perspective about the preservation of wildlife and biodiversity protection. Through the approach of Qur'anic studies, this research identifies ecological values and teachings that encourage human responsibility towards nature. Methodology: With the kind of library research or literature study, a qualitative research methodology is applied. The research method involves analyzing Qur'anic texts related to the environment, wildlife, and biodiversity, focusing on concepts such as khalifa (earth-sustainer) and amanah (responsibility). In this study also used a semantic approach that is useful in analyzing Qur'anic verses about ecology. Results: The results showed that the Qur'an contains values that support the protection and preservation of wildlife and biodiversity. The implications of these findings could provide a basis for the development of environmental protection strategies rooted in Islamic values. Applications/Originality/Value: This research is expected to provide a better understanding of the relationship between religious teachings and biodiversity, lead to ecological awareness in daily religious practice, as well as provide a basis for Islamic-based nature conservation advocacy.